(untitled) (Journal of Special Education and Rehabilitation, 2013)
The Master’s thesis is presented on 117 pages. The paper contains the following sections: introduction, theoretical approach to the problem of the research, analysis and interpretation of results, conclusions with proposed measures, literature and articles. The introduction emphasizes the stereotype about people with disabilities in our society, the widespread discrimination and stigmatization as fundamental barriers in the social inclusion of people with disabilities. The high degree of prejudice, the architectural barriers and the indifferent attitude of the state restricts the fundamental rights and freedoms of persons with disabilities. Young people with disabilities do not always have conditions and opportunities to participate actively in all spheres of social life, as the other citizens.